2006
DOI: 10.1083/jcb.200512142
|View full text |Cite
|
Sign up to set email alerts
|

PI4P-signaling pathway for the synthesis of a nascent membrane structure in selective autophagy

Abstract: Phosphoinositides regulate a wide range of cellular activities, including membrane trafficking and biogenesis, via interaction with various effector proteins that contain phosphoinositide binding motifs. We show that in the yeast Pichia pastoris, phosphatidylinositol 4′-monophosphate (PI4P) initiates de novo membrane synthesis that is required for peroxisome degradation by selective autophagy and that this PI4P signaling is modulated by an ergosterol-converting PpAtg26 (autophagy-related) protein harboring a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 31 publications
0
76
0
1
Order By: Relevance
“…It could be that the amount of sterol glucoside (SG) in S. cerevisiae 13 is too low to have any effect on these autophagy-related pathways. SG synthesis is higher in P. pastoris, and the SG content might influence MIPA formation and other membrane events in P. pastoris, which contributes to the involvement of PpAtg26 in pexophagy; 5 however, the role of the S. cerevisiae Atg26 protein, remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the amount of sterol glucoside (SG) in S. cerevisiae 13 is too low to have any effect on these autophagy-related pathways. SG synthesis is higher in P. pastoris, and the SG content might influence MIPA formation and other membrane events in P. pastoris, which contributes to the involvement of PpAtg26 in pexophagy; 5 however, the role of the S. cerevisiae Atg26 protein, remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…4 PpAtg26 is also required for the formation of the MIPA structure. 5 The three domains of PpAtg26, pleckstrin homology (PH), GRAM and catalytic UDP-glucosyl transferase (UDPGT) domains, are all essential for microautophagy. 4 However, in the alkane-utilizing yeast Yarrowia lipolytica, it is not required for pexophagy.…”
Section: Introductionmentioning
confidence: 99%
“…The sterol glucosyltransferase Atg26 is also crucial for the generation of the MIPA (Oku et al 2003). Upon micropexophagy induction, the synthesis of phosphatidylinositol-4-phosphate at the site where the MIPA will emerge leads to the recruitment of Atg26 through its GRAM domain, which specifically binds to this lipid, and permits the local production of ergosterol glucoside (Oku et al 2003;Yamashita et al 2006). The function of this molecule in micropexophagy, however, is unclear and it appears to be essential only for glucose-induced micropexophagy, but not when the same pathway is triggered by oleate or amine (Nazarko et al 2007).…”
Section: Macroautophagymentioning
confidence: 99%
“…Therefore, we examined the trafficking of Atg9p and Atg11p, and we showed that their trafficking to the sequestering membranes was unaffected by the Sar1p mutants. The MIPA assembles from the PAS or initiation complex, a structure that contains Atg8p and Atg17p Yamashita et al, 2006). The formation of the MIPA is influenced by many Atg proteins, including Atg8p and Atg26p and the availability of lipids such as PE and phosphatidylinositol 4Ј-monophosphate (PI4P) (Yamashita et al, 2007).…”
Section: Role Of Sar1p In Micropexophagymentioning
confidence: 99%